Individual behavioural counselling for smoking cessation. - Lancaster, T; Stead, L (2000)
BACKGROUND: Individual counselling from a smoking cessation specialist may help smokers to make a successful attempt to stop smoking. OBJECTIVES: The objective of the review is to determine the effects of individual counselling. SEARCH STRATEGY: We searched the Cochrane Tobacco Addiction Group trials register for studies with counsel* in any field. Date of the most recent search: October 1998. SELECTION CRITERIA: Randomised or quasi-randomised trials with at least one treatment arm consisting of face to face individual counselling from a health care worker not involved in routine clinical care. The outcome was smoking cessation at follow-up at least six months after the start of counselling. DATA COLLECTION AND ANALYSIS: Both reviewers extracted data. The intervention and population, method of randomisation and completeness of follow-up were recorded. MAIN RESULTS: We identified eleven trials. Ten compared individual counselling to a minimal intervention, two compared two intensities of counselling, and one compared individual counselling to group therapy. Individual counselling was more effective than control. The odds ratio for successful smoking cessation was 1.55 (95% confidence interval 1.27 to 1.90). There was no evidence that more intensive counselling was more effective than brief counselling (odds ratio 1.17, 95% confidence interval 0.59 to 2.34). There was no evidence of a difference in effect between individual counselling and group therapy (odds ratio 1.33, 95% confidence interval 0.83 to 2.13). REVIEWER'S CONCLUSIONS: Smoking cessation counselling can assist smokers to quit.